Pengaruh Kredibilitas, Kualitas Pendekatan Emosional, Dan Kualitas Isi Pesan Terhadap Efektivitas Kampanye “Love Myself” - Antonia Meme (Universitas Gadjah Mada, 2021)
A successful social campaign was created from elements such a specific targeted audience, campaign messages, developed theory of change, and use a proper communicator. The elements formulated in the rhetoric theory: credibility, emotions, messages. The elements were conducted in a campaign called “Love Myself” by BTS, a K-pop group. This study was conducted to figure out the effect of credibility, the quality of the emotional approach, and the quality of the messages from K-pop group BTS on the effectiveness of the campaign “Love Myself”. This study uses a rhetoric theory that focuses on the aspects of ethos (credibility), pathos (emotions), and logos (logic). This study uses a survey method, especially an online questionnaire. Non-probability sampling is a sampling technique where not every population has a chance to become a sample. Quota sampling where the quota set first by the researcher. The population is total followers of Twitter account @armyindonesiaa2 and the number of sampling, 395. The analysis technique uses path analysis. The result presents the final model where six relation variables are not significant. Based on the test model, the final model is no longer suitable for use as a research model compared to the hypothetical model. The largest total effect result, forming from variable effectiveness of the campaign “Love Myself”. The process of this research concluded that the credibility and emotional approach of K-pop group BTS has no contribution to the effectiveness of the campaign “Love Myself”.